Daily oscillation of the excitation/inhibition ratio is disrupted in two mouse models of autism - Michelle C.D. Bridi; Nancy Luo; Grace Kim; Benjamin J. Menarchek; Rachel A. Lee; Bryan Rodriguez; Daniel Severin; Christian Wesselborg; Caroline O’Ferrall; Ruchit Patel; Sarah Bertrand; Sujatha Kannan; et al. (iScience)
Summary: Alterations to the excitation/inhibition (E/I) ratio are postulated to underlie behavioral phenotypes in autism spectrum disorder (ASD) patients and mouse models. However, in wild type mice the E/I ratio is not constant, but instead oscillates across the 24-h day. Therefore, we tested whether E/I regulation, rather than the overall E/I ratio, is disrupted in two ASD-related mouse lines: Fmr1 KO and BTBR, models of syndromic and idiopathic ASD, respectively. The E/I ratio is dysregulated in both models, but in different ways: the oscillation is lost in Fmr1 KO and reversed in BTBR mice. Phenotypes in both models associate with differences the timing of excitatory and inhibitory synaptic transmission and endocannabinoid signaling compared to wild type mice, but not with altered sleep. These findings raise the possibility that ASD-related phenotypes may be produced by a mismatch between E/I and behavioral state, rather than alterations to overall E/I levels per se.